Pengaruh Good Governance Dan Standar Akuntansi Pemerintah Pada Kualitas Informasi Keuangan - Nurharibnu Wibisono; Fatchur Rochman; Rhoman Syafi’i (Universitas Merdeka Madiun, 2026)
The aim of this study is to examine how Good Governance and the application of Government Accounting Standards (GAS) affect the quality of financial information. This study employs a quantitative approach. This research is quantitative with multiple regression methods and data processing using SPSS tools. The population is the financial management apparatus in 15 (all) sub-districts of Madiun Regency. Purposive sampling was determined, namely 2 (two) financial management tools for finance, program preparation and reporting in 15 sub-districts of Madiun Regency, totaling 30 respondents. The findings reveal that Good Governance and GAS each positively and significantly affect the Quality of Financial Information in the sub-districts of Madiun Regency. Moreover, when both variables are considered together. Good Governance and GAS also produces a positive and significant influence on the quality of financial information. The adjusted R2 value is 0.626, indicating that together Good Governance and SAP implementation influence KIK by 62.6% and the remaining 37.4% is influenced by other variables, such as the Internal Supervisory Unit (SPI), competency, and so on. Practical contribution, as implementer of public policy, the District Government needs to be consistent in implementing Good Governance and SAP so that it can produce quality financial information that shows good service performance to the community. Based agency theory, as a development agent, the District Government must be able to carry out its mandate to manage public financial resources with the aim of achieving a just and prosperous society.